PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS X SMA N 5 MERANGIN - Karnika, Loli (STKIP YPM Bangko, 2018)
This study aims to describe mathematical communication skills using the cooperative learning model type make a match better than conventional learning class X SMA N 5 Merangin. This study uses a quantitative approach, an experimental method with a population of students in class XA, XB, XC and XD. The sampling technique uses simple random sampling technique. The sample chosen was XB class as the experimental class and XC class as the control class. The technique of collecting data through tests of mathematical communication skills with essay questions on three dimensional space material. Requirement test results of data are normally distributed and homogeneous variance, then the data analysis technique used is the t-test (independent sample t-test). From the analysis of the final test data on the experimental class obtained an average of 46,172, while the control class obtained an average of 35,893. Hypothesis test results obtained tcount = 8.533 and = 1.673, because tcount > then Ha is accepted namely mathematical communication skills using the cooperative learning model type make a match better than conventional learning class X SMA N 5 Merangin The recommendation of this study is the Make A Match type cooperative learning model that is better applied in the learning process in three dimensional space material, because this learning model can make students more active and able to develop themselves.